Corporate Governance Issues and Challenges in India: भारत में कॉर्पोरेट प्रशासन के मुद्दे और चुनौतियाँ - Yadav, Rakesh (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Corporate governance fundamentally revolves around how corporations are directed, managed, controlled, and held accountable to their shareholders. In India, the question of corporate governance emerged primarily in the context of economic liberalization and the regulation of industry and trade. With the rapid pace of globalization, many companies have been compelled to tap into international financial markets, subsequently facing greater competition than ever before. Policymakers and business managers alike have become increasingly aware of the importance of improved corporate governance standards. Abstract in Hindi Language: कॉर्पोरेट प्रशासन मूल रूप से इस बारे में है कि निगमों को कैसे निर्देशित, प्रबंधित, नियंत्रित और उनके शेयरधारकों के प्रति उत्तरदायी बनाया जाता है। भारत में, कॉर्पोरेट प्रशासन का प्रश्न मुख्य रूप से आर्थिक उदारीकरण और उद्योग और व्यापार के विनियमन के मद्देनजर सामने आया है। वैश्वीकरण की तीव्र गति के साथ कई कंपनियों को अंतरराष्ट्रीय वित्तीय बाजारों का दोहन करने और इसके बाद पहले की तुलना में अधिक प्रतिस्पर्धा का सामना करने के लिए मजबूर होना पड़ा है। नीति निर्माता और व्यवसाय प्रबंधक दोनों ही कॉर्पोरेट प्रशासन के बेहतर मानकों के महत्व के बारे में तेजी से जागरूक हो गए हैं। Keywords: भारत, कॉर्पोरेट प्रशासन, आर्थिक उदारीकरण, उद्योग और व्यापार।